Therapy in cancer 2008: quo vadis? - Clark, Jeffrey (Henry Stewart Talks, 2009)
Why pursuing new therapeutic approaches in cancer is important, Prevention and screening, Current cancer therapy: non-surgical, Most chemotherapy targets DNA, Chemotherapy effects, Current state of cancer therapy: efficacy and toxicity, Molecular pathogenesis of cancer, Pursuing targeted therapy in cancers, Targeted biologic therapies, Evolving targets and agents, Shift from chemotherapy to targeted agents, Clinically established molecular targets in malignancies, Targeted therapy: proteins and small molecules, Changes brought about by targeting: efficacy and toxicity, Biomarkers in drug development, What is currently known: angiogenesis, The VEGF family and its receptors, Bevacizumab and Sorafenib, Does toxicity correlate with response?, What research is ongoing: agents?, Future directions in cancer treatment options, Core pathways altered in pancreatic and colorectal cancer, Implications of genetic sequencing of solid tumors to date, Epigenetics and cancer therapy
Archived at 2021/02/25